Fossils from a Rural Past : A Study of Extant Cantonese Children's Songs - Kwok, Helen (Book collections on Project MUSE., 1990)
A selection of popular extant Cantonese children's songs, studying both their linguistic and non-linguistic aspects. The Chinese texts of the songs are printed together with their English translations.